Modeling ultrasonic compression wave absorption during the seeded crystallization of copper (II) sulphate pentahydrate from aqueous solution - Marshall, Thomas (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2002)
Ultrasonic compression wave absorption is investigated as a means to monitor the seeded crystallization of copper (II) sulphate pentahydrate from aqueous solution. Simple models are applied to predict crystal yield, crystal size distribution, and the changing nature of the continuous phase. The Allegra-Hawley scattering formulation is used to simulate ultrasonic absorption as crystallization proceeds. Experiments confirm that simulated attenuation is in agreement with measured results